Crystallization behavior of WO3-MoO3-TeO2 glasses - Gedikoglu, N.; Ersundu, A. E.; Aydin, S.; Celikbilek Ersundu, M. (ELSEVIER SCIENCE BV, 2018)
In the present study, crystallization behavior of tungsten molybdenum tellurite glasses was investigated by non isothermal methods using differential scanning calorimetry (DSC), X-ray diffraction (XRD), energy dispersive Xray spectroscopy (EDS) and scanning electron microscopy (SEM) techniques. Thermal properties of glasses were investigated to calculate the values of glass transition temperature (T-g), crystallization temperature (T-c/T-p), temperature difference (Delta T), thermal stability (S), glass transition activation energy (E-g) and fragility parameter (m). Average cross-link density ((n(c)) over bar) values were calculated for the physical investigation of the glasses. The crystallization kinetics was studied at different heating rates and the values of Avrami constant (n) and morphology index (m) were calculated from the Ozawa equation and the activation energy of crystallization (E-c) was determined using the modified Kissinger equation. The crystallized and/or transformed phases and their morphologies were determined by XRD and SEM analysis. Studied glass compositions were found to be thermally stable, resistant to crystallization and therefore suitable for opto-electronic applications.
Keywords: Tellurite glasses; Crystallization kinetics; Non-isothermal methods; DSC; THERMAL-PROPERTIES; OPTICAL-PROPERTIES; TELLURITE; KINETICS; TRANSITION; CONDUCTIVITY; TEMPERATURE; STABILITY; FRAGILITY; BINARY; Materials Science